Changing Inequality in Five Countries: The Role of Markets, Transfers and Taxes - Markus Jäntti (Luxembourg Income Study (LIS), 1993)
Using LIS data the author explores the possibility that markets, the public sector, or demographic shifts affect the changing distribution of income among families in five industrialized countries in the 1980s.
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; Großbritannien; Kanada; Niederlande; Schweden; USA